2019
DOI: 10.1002/cam4.2731
|View full text |Cite
|
Sign up to set email alerts
|

Use of artificial nutrition near the end of life: Results from a French national population‐based study of hospitalized cancer patients

Abstract: Background:The use of artificial nutrition, defined as a medical treatment that allows a non-oral mechanical feeding, for cancer patients with limited life expectancy is deemed nonbeneficial. High-quality evidence about the use of artificial nutrition near the end of life is lacking. This study aimed (a) to quantify the use of artificial nutrition near the end-of-life, and (b) to identify the factors associated with the use of artificial nutrition. Methods: This was a retrospective cohort study of decedents ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…The use of EN and PN in the PCU in our study was similar to that reported by Kempf et al 20 . and higher than that found by Baumstarck et al 12 . Previous studies have also noted that health professionals from care homes and centers specialized in palliative care are more concerned with the implications generated by NS in the last weeks of life, being more conservative in its prescription 22,23 …”
Section: Discussionsupporting
confidence: 89%
“…The use of EN and PN in the PCU in our study was similar to that reported by Kempf et al 20 . and higher than that found by Baumstarck et al 12 . Previous studies have also noted that health professionals from care homes and centers specialized in palliative care are more concerned with the implications generated by NS in the last weeks of life, being more conservative in its prescription 22,23 …”
Section: Discussionsupporting
confidence: 89%
“…It is already known that younger age and male gender are associated with higher rates of artificial nutrition. 33 However, even after adjustment for these parameters, patients within specialized palliative homecare showed a higher probability for parenteral nutrition. This possible overprovision within specialized palliative homecare should be analyzed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized prospective trial showed that home parenteral nutrition may have advantages, prolonging survival and improving quality of life in malnourished patients receiving home-based palliative care [ 80 ]. Other reports, however, indicate that the use of artificial nutrition, defined as a medical treatment that allows a non-oral mechanical feeding, in the end of life care is limited to 3% of the patients [ 81 ]. Despite this remains an unresolved issue [ 82 , 83 ], a tailored approach to optimize resources in every single patient is highly desirable.…”
Section: Nutritional Care During Later Treatment Lines and Beyond: Is The Final Hurdle Worth Jumping?mentioning
confidence: 99%